Ritual als Resonanzerfahrung - Rüpke, Jörg (W. Kohlhammer GmbH, 2021)
Ritual and ritualization have become central concepts in cultural and social studies. This book shows why it is productive neither to equate ritual and religion, nor to simply abandon the concept of religion. Conceiving of religion as communicative action allows ritual to be understood as a form of listening to the world and as a form of changing the world. The book=s primary intention is not to make a contribution to theory, but rather to demonstrate & through example analyses of a wide variety of rituals & the fruitfulness of an approach that links elements of classical theories of ritual to more recent concepts of religion and to the basic idea of the mutual constitution of subjects and objects. Ritual und Ritualisierung sind zu zentralen Begriffen der Kultur- und Gesellschaftswissenschaften geworden. Das Buch zeigt, warum es fruchtbar ist, weder Ritual und Religion gleichzusetzen noch den Begriff der Religion einfach fallen zu lassen. Religion als kommunikatives Handeln zu verstehen, lässt Ritual als eine Form des Zuhörens auf die Welt und als eine Form der Veränderung der Welt begreifen. Dieses Buch will nicht in erster Linie einen Theorie-Beitrag liefern, sondern in der exemplarischen Analyse verschiedenster Rituale die Fruchtbarkeit eines Zugriffs vorführen, der Elemente klassischer Ritualtheorien mit neueren Religionsbegriffen sowie mit dem Grundgedanken der wechselseitigen Konstituierung von Subjekten und Objekten verknüpft